Sally Hawkins, Ian Convery, Steve Carver and Rene Beyers (eds.), "Routledge Handbook of Rewilding" - Cary, Emma (Journal for the study of religion, nature and culture, 2025)
Sally Hawkins, Ian Convery, Steve Carver and Rene Beyers (eds.), Routledge Handbook of Rewilding (London: Routledge, 2023), xxiii + 395 pp., $ 54.00 (pbk), ISBN: 978-0-367-56449-0.